2013
DOI: 10.1016/j.jeem.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Renewable electricity policies, heterogeneity, and cost effectiveness

Abstract: Renewable electricity policies promote investment in renewable electricity generators and have become increasingly common around the world. Because of intermittency and the composition of other generators in the power system, the value of certain renewables-particularly wind and solar-varies across locations and technologies. This paper investigates the implications of this heterogeneity for the cost effectiveness of renewable electricity prices as compared to one another and to a carbon dioxide emissions pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 21 publications
1
58
0
Order By: Relevance
“…Within the electricity sector, some of the societal costs of fossil generation -such as air pollution, greenhouse gas emissions, water usage, and fuel supply risk (i.e., fuel price volatility as well as geopolitical risk) -are, arguably, not fully reflected in market prices, leading to inefficient choices for energy supply. Though addressing these market failures directly through policies that are specifically intended to internalize external costs is generally expected to be more cost-effective (e.g., Fell andLinn 2013, Fischer andNewell 2008), governments instead often use incentives for the deployment of renewable generation to pursue similar societal objectives: reduced air emissions, mitigation of climate change impacts, reduced water usage, and a more-balanced electricity supply portfolio (IPCC 2011).…”
Section: Rationale For Federal Incentivesmentioning
confidence: 99%
“…Within the electricity sector, some of the societal costs of fossil generation -such as air pollution, greenhouse gas emissions, water usage, and fuel supply risk (i.e., fuel price volatility as well as geopolitical risk) -are, arguably, not fully reflected in market prices, leading to inefficient choices for energy supply. Though addressing these market failures directly through policies that are specifically intended to internalize external costs is generally expected to be more cost-effective (e.g., Fell andLinn 2013, Fischer andNewell 2008), governments instead often use incentives for the deployment of renewable generation to pursue similar societal objectives: reduced air emissions, mitigation of climate change impacts, reduced water usage, and a more-balanced electricity supply portfolio (IPCC 2011).…”
Section: Rationale For Federal Incentivesmentioning
confidence: 99%
“…The specific costs and benefits of increased wind development will be impacted by the nature of the policy and market levers used to encourage that development; as such, the present work suggests the general magnitude of these impacts only. Related research has found that policies specifically designed to internalize external costs and correct for market failures are likely to be more cost effective than technology-or sector-specific policy incentives, in part due to possible economy-wide rebound and spillover effects and also because such policies more-directly target the achievement of public benefits (Borenstein 2012;Edenhofer et al 2013;Fischer and Newell 2008;Fell and Linn 2013;IPCC 2011;IPCC 2014b;Kalkuhl et al2013;McKibbin et al 2014;Novan 2014;Rausch and Karplus 2014;Tuladhar et al 2014). Therefore, while the present analysis may suggest a significantly positive role for wind energy, achieving those benefits to the maximum and most cost-effective degree is likely to require a policy framework that moves away from direct support of wind to one that more effectively and more broadly addresses key market failures and unpriced externalities.…”
Section: Resultsmentioning
confidence: 99%
“…This is partly due to possible economy-wide rebound, spillover, or leakage effects, and also because such policies more directly target the achievement of public benefits (Borenstein 2012;Edenhofer et al 2013;IPCC 2011;IPCC 2014;Kalkuhl et al 2013;McKibbin et al 2014;Tuladhar et al 2014). Research focused on RPS policies has highlighted these possible effects, finding that the desired benefits of RPS programs may not be fully achieved or achieved as cost effectively as might be desired (Bushnell et al 2007;Carley 2011;Fischer and Newell 2008;Fell and Linn 2013;Rausch and Karplus 2014), though other research suggests that the pitfalls of such "second-best" policies may be modest (Kalkuhl et al 2012). …”
Section: General Limitationsmentioning
confidence: 99%